Driving Educational Institutions: A Case Study on Instructional Leadership in a Public School of Sindh, Pakistan - Sarhandi, Pir Suhail Ahmed; Bugti, Sana Mairaj; Bugti, Firdous (Journal of Development and Social Sciences, 2025)
Leadership serves as a catalyst that significantly improves educational outcomes. Twenty first century principals are considered as instructional leaders. Instructional leadership is a crucial approach in educational management that aims to enhance teaching and learning within schools. It emphasizes the principal’s responsibilities in establishing academic objectives, directing curriculum design, monitoring student learning progress, and creating a supportive learning atmosphere. The purpose of this qualitative study was to explore the dimension of instructional leadership at a public school in district Khairpur. The philosophical view of this research comprised of constructivist and interpretivist paradigms. A principal and a senior teacher were purposively selected as samples of the study. The data was collected through semi-structured in-depth interviews. The collected data was analyzed thematically which yielded three major themes 1) Vision/Mission of the school, 2) Managing the instructional program and 3) Creating positive school climate. The study recommends that future studies may explore other dimensions of instructional leadership from the perspective of different models by acceding the population and by using different methodology.